Two Successive Type II Radio Bursts Associated With B-Class Flares and Slow CMEs - Ma, Suli; Chen, Huadong (Frontiers in Astronomy and Space Sciences, 2020)
3 From 2018 Oct 12 to 13, three successive solar eruptions (E1–E3) with B-class flares and poor 4 white light coronal mass ejections (CMEs) occurred from the same active region NOAA AR 12724. 5 Interestingly, the first two eruptions are associated with Type II radio bursts but the third is not. 6 Using the soft X-ray flux data, radio dynamic spectra and dual perspective EUV intensity images, 7 we comparatively investigate the three events. Our results show that their relevant flares are weak 8 (B2.1, B7.9 and B2.3) and short-lived (13, 9 and 14 minutes). The main eruption directions of 9 E1 and E2 are along CAN45SO north of their radial directions, while E3 primarily propagated along 10 the radial direction. In the EUV channels, the early speeds of the first two CMEs have apparent 11 speeds of CAN320 km s1 and CAN380 km s1, which could exceed their respective local AlfveDC3n 12 speeds of CAN300 km s1 and CAN350 km s1. However, the CME in the third eruption possesses a 13 much lower speed of CAN160 km s1. These results suggest that the observed Type II radio bursts 14 in the eruptions E1 and E2 are likely triggered by their associated CMEs and the direction of 15 eruption and the ambient plasma and magnetic environments may take an important place in 16 producing Type II radio burst or shock as well.